2018
DOI: 10.1016/j.synbio.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Engineering metabolic pathways in Amycolatopsis japonicum for the optimization of the precursor supply for heterologous brasilicardin congeners production

Abstract: The isoprenoid brasilicardin A is a promising immunosuppressant compound with a unique mode of action, high potency and reduced toxicity compared to today's standard drugs. However, production of brasilicardin has been hampered since the producer strain Nocardia terpenica IFM0406 synthesizes brasilicardin in only low amounts and is a biosafety level 2 organism. Previously, we were able to heterologously express the brasilicardin gene cluster in the nocardioform actinomycete Amycolatopsis japonicum. Four brasil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We got 5–10 colonies per plate when hmgs , hmgr , or crtZ was overexpressed, while less than 5 colonies per plate were obtained when either idi , crtE , or crtIBY was expressed. This suggests that overexpressing endogenous idi , crtE , or crtIBY alone might affect the recovery of the colonies, probably via the accumulation of excess toxic intermediates such as IPP, DMAPP, and GGPP. HPLC results showed that overexpressing hmgs , hmgr , idi , crtE , crtIBY , or crtZ individually in strain M326 all led to increased astaxanthin levels when compared with those in strain M326 (Figure c,d). Although the biomass was slightly reduced in all transformants, both the astaxanthin titer and yield of each transformant were increased, especially by overexpressing hmgr , idi , or crtE (Figure c).…”
Section: Resultsmentioning
confidence: 97%
“…We got 5–10 colonies per plate when hmgs , hmgr , or crtZ was overexpressed, while less than 5 colonies per plate were obtained when either idi , crtE , or crtIBY was expressed. This suggests that overexpressing endogenous idi , crtE , or crtIBY alone might affect the recovery of the colonies, probably via the accumulation of excess toxic intermediates such as IPP, DMAPP, and GGPP. HPLC results showed that overexpressing hmgs , hmgr , idi , crtE , crtIBY , or crtZ individually in strain M326 all led to increased astaxanthin levels when compared with those in strain M326 (Figure c,d). Although the biomass was slightly reduced in all transformants, both the astaxanthin titer and yield of each transformant were increased, especially by overexpressing hmgr , idi , or crtE (Figure c).…”
Section: Resultsmentioning
confidence: 97%
“…Transcription analysis will help to identify the most competing pathways. Moreover, pathway genes of the primary metabolism such as the mevalonate pathway are now accessible and allow for a targeted manipulation of metabolic fluxes towards terpenoid biosynthesis [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent use of heterologous host systems and genetic manipulations of the regulatory genes and precursor pathways turned out to be efficient in the improvement of production yield of brasilicardin congeners [8,56], serving as a starting point for a semi-synthetic approach. The latest advances in the total synthesis of brasilicardins (however, limited by low total yield) [57,58] combined with a biosynthetic approach could allow further improvement of the The average values of three technical replicates obtained for each strain were normalized to A. japonicum::pPS1+pIJ (100%), standard deviations were calculated using Excel spreadsheet and are presented on the graph production yields.…”
Section: Discussionmentioning
confidence: 99%